I'll (Always) Be Back: Virtual Performance and Post-Human Labor in the Age of Digital Cinema. - Sperb, Jason (Culture, Theory & Critique, 2012)
This essay explores recent trends in digital production towards the use of ‘virtual performances’ in Hollywood films and commercials. This involves the use of computer-generated imagery, motion-capture performance and other pro-filmic elements to create a digital character, such as a virtual Arnold Schwarzenegger as the iconic ‘Terminator’, in Terminator: Salvation (2009). The trend began in the early 1990s, using recycled footage of dead classic movie stars, such as Fred Astaire or Humphrey Bogart, in television commercials – a fitting beginning for an artistic innovation which largely reduces star power to its crudest exchange value. More recently, virtual performances have brought ‘back to life’ Laurence Olivier in Sky Captain and the World of Tomorrow (2004) and Marlon Brando in Superman Returns (2006). Such novelty seems little more than a passing attraction at present, a way for the latest Hollywood blockbuster to distinguish itself in a crowded marketplace. Yet, it serves as a powerful opening into larger discussions about the impact of technological innovations on labor practices in a post-Fordist globalised economy, as well as shifts in the relationship to film history and stardom in the age of digital cinema. As a historical referent, this essay ends with an extensive examination of Michael Crichton's Looker (1981), a dystopic science fiction film about post-human labor in the age of late capitalism. The film narrativises a corporation's desire to convert beautiful glamour models into computer programs, thereby providing an endless supply of free and infinitely malleable performances in the service of postmodern American advertising culture. What seemed impossibly futuristic in 1981 acquires increasing viability just three decades later in an age of virtual performance.